BUILDING NAGARI IN IMPROVING TOURISM AND EMPOWERING ENVIRONMENTALLY CONSCIOUS COMMUNITIES IN LAMBUNG BUKIK DISTRICT, PAUH DISTRICT, PADANG CITY - Meriyani, Meriyani; Yulia Syafitri; Meri Dwi Anggraini; Andre Bustari; Afrizal Yulianto Saputra (Ikatan Dosen Menulis, 2024)
Lambung Bukik Village in Padang City, West Sumatra, has great potential for community-based tourism development. This article aims to examine strategic approaches in empowering local communities through sustainable tourism. This study uses a participatory method by involving local communities in every stage of development, from planning to implementation. The results show that a community-based approach can increase environmental awareness, optimize local economic potential, and encourage active community participation in sustainable natural resource management. Recommendations include community training, strengthening local institutions, and collaboration with the private sector and government.